2022
DOI: 10.3390/ijerph19010548
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Consumption of Drugs Prescribed for the Treatment of Asthma in Belgian Children

Abstract: (1) Asthma is one of the most common chronic diseases in the world among children. The main purpose of this study was to analyze the consumption of asthma medications in order to investigate asthma in children (2–18 years) and the association with health care consumption; (2) a retrospective study using anonymized administrative data for 2013–2018 from the third largest Belgian health insurer was conducted; (3) in 2018, 12.9% of children received at least one asthma medication and 4.4% received at least two pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…For children under the age of five with asthma, daily low doses of ICS were recommended for the second step of the treatment. It has already been shown that young children (2–6 years) were more likely to receive asthma medications such as ICS than older children [ 22 ]. However, for these young children, the diagnosis of asthma is difficult to establish because of the non-specificity of the symptoms and the lack of tests available for these symptoms [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…For children under the age of five with asthma, daily low doses of ICS were recommended for the second step of the treatment. It has already been shown that young children (2–6 years) were more likely to receive asthma medications such as ICS than older children [ 22 ]. However, for these young children, the diagnosis of asthma is difficult to establish because of the non-specificity of the symptoms and the lack of tests available for these symptoms [ 23 ].…”
Section: Discussionmentioning
confidence: 99%